Seasonal Variation in Months of Birth and Symptom Flares in Korean Patients with Inflammatory Bowel Disease (Gut and Liver, 2013)
Background/AimsSeasonal variation may influence the development and exacerbation of inflammatory bowel disease (IBD). However, most epidemiologic studies on this topic have been conducted in Western countries. The purpose of this study was to determine whether birth dates and symptom flares follow a seasonal pattern in Korean patients with IBD.Methods : Patients with a diagnosis of IBD established between January 2003 and December 2010 were investigated at six university hospitals in Korea. The expected births and flares, with a uniform distribution during the year and considering differences in the number of days in the months of 1 year, were calculated.Results : A total of 411 patients with ulcerative colitis (UC) and 316 patients with Crohn disease (CD) were included in the study. Birth during the winter period, and especially in January and February, was associated with an increased risk of IBD, especially in UC patients. The symptom flares of CD patients occurred most frequently in the spring, with a nadir in the autumn. However, no disease flare seasonality was noted for UC patients.Conclusion : sOur data suggest that seasonally varying environmental factors during pregnancy and the postpartum period are associated with a susceptibility to IBD later in life and that exacerbations of CD are influenced by seasonal factors.